«Գինի» բառն ուրարտերենում - Երվանդ Գրեկյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Несмотря на то, что во многих языках слова “виноград” и “вино” синонимичны, как, например, акк. ka/iranu, которое обозначает и “вино”, и “виноград”, и “виноградник”, ни одно из слов haluli (“виноград, виноградная лоза” ), (GIS)uldi(=GISuduli(?))/GISG ESTIN (“виноградная лоза, виноградник” ), словоформа G^urtan i (“виноградная лоза, саженец винограда), часто встречающиеся в урартских текстах, не претендует на то, чтобы выразить смысл слова “вино” в урартском языке. While in many languages the words for‘ grape’ and ‘wine’ are identical, as, for example, ka/iran u in Akkadian, which means ‘wine, ‘grape, and ‘vine(yard)’ sim ultan eously, none of the words haluli (‘grape, ‘vine’), (GIS)uldi (= GISuduli(?))/GISG ESTIN (‘vine,‘vineyard ’) and GISurtani (‘vine, ‘grap evine’) appearing frequently in Urartian texts is a candidate for the meaning for ‘wine’ in Urartian language.
Keywords: Philology; Linguistics; Language and Literature; Liturgy and Ritual